2008
DOI: 10.1055/s-2007-989453
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Lactate Threshold Using Ventilatory Threshold

Abstract: Lactate threshold is an important reference point when setting training intensities for endurance athletes. Ventilatory threshold has been used as a noninvasive estimate of lactate threshold, but appears to underestimate training intensity for many athletes. This study evaluated whether data obtained during a noninvasive, maximal exercise test could be used to predict lactate threshold. Maximal oxygen consumption (55+/-2 ml O(2) x kg(-1) x min(-1)) and heart rate at the ventilatory threshold (V-slope method) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
(44 reference statements)
1
13
1
2
Order By: Relevance
“…9,54,55 In order to take into account the lactate kinetics of individuals, individual AT concepts such as the Dm-AT have also been used to obtain threshold values on a rowing ergometer. 16,22,35,56 Although the two criterion indices (La4-At and Dm-AT) in the present study differed slightly with respect to blood lactate concentration, VO 2 , PO and HR, the yielded AT values were highly correlated, both with each other and with the four different noninvasive indices. Interestingly, the mean 3.65 mmol/l value found for Dm-AT in the present study was very close to that reported by Jürimäe et al 19 (3.7 mmol/l) using a logarithmic method for determining individual AT; AT log is the PO at which blood lactate begins to increase when log [blood lactate] is plotted against log [power output] .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…9,54,55 In order to take into account the lactate kinetics of individuals, individual AT concepts such as the Dm-AT have also been used to obtain threshold values on a rowing ergometer. 16,22,35,56 Although the two criterion indices (La4-At and Dm-AT) in the present study differed slightly with respect to blood lactate concentration, VO 2 , PO and HR, the yielded AT values were highly correlated, both with each other and with the four different noninvasive indices. Interestingly, the mean 3.65 mmol/l value found for Dm-AT in the present study was very close to that reported by Jürimäe et al 19 (3.7 mmol/l) using a logarithmic method for determining individual AT; AT log is the PO at which blood lactate begins to increase when log [blood lactate] is plotted against log [power output] .…”
Section: Discussioncontrasting
confidence: 55%
“…This method, termed Dmax, was found to be an objective and reliable method for LT determination. 21,22 In order to avoid expensive invasive procedures, investigators have attempted to predict AT values from physiological measurements obtained during a noninvasive single-graded exercise test. Popular non-invasive AT procedures during different ergometries involve the use of either respiratory data or simply the HR curve.…”
Section: Introductionmentioning
confidence: 99%
“…Other indirect methods to estimate such thresholds use pulmonary gas exchange data (40,49) (i.e., ventilatory threshold) or electromyographic signals (40). Several studies have aimed to compare different methods to determine the lactate and ventilatory thresholds using different protocols (9,11,35,40), although it is difficult to draw conclusions, as the results heavily depend on the specific methodologies used (e.g., cycle or treadmill, duration of exercise stage, blood sampling site). Others have attempted to investigate the relationship between lactate or ventilatory threshold and exercise performance in thermoneutral conditions (6,19,50).…”
mentioning
confidence: 99%
“…Indeed, 'LT2 testing' is a central measurement tool used by institutes and academies of sport throughout Australia and around the world to gauge the 'fitness' of their endurance athletes at a particular point in time. It is also used to establish endurance performance status [9][10][11] , to prescribe training zones [12,13] to enable athletes to improve their endurance capacity and to monitor changes in response to training [12][13][14] . Moreover, the relationship between LT2 and endurance performance appears to be stronger than the V O2max-endurance performance relationship in trained endurance athletes.…”
Section: Fractional Utilisation Of V O 2 Maxmentioning
confidence: 99%
“…The LT2 is commonly used to establish endurance performance status [9][10][11] , prescribe training zones [12,13] and monitor changes in response to training [12][13][14] .…”
Section: Introduction To the Research Problemmentioning
confidence: 99%